Exploration of Customer Experience in Satisfaction and Loyalty Toward Lion Air Flight Services - Betrin Loreva Sipayung; Tongam Sirait (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Lion Air is one of the leading airlines in Indonesia's low-cost carrier (LCC) market. However, the airline faces several public concerns related to service quality and customer experience. This study aims to explore the reasons behind customer retention and the dynamics of customer satisfaction in the face of operational shortcomings. The study employs a qualitative approach to explore and understand customer experiences, perceptions, and preferences in-depth. Data were collected through primary and secondary sources, and interviews were conducted with participants. Data analysis was conducted qualitatively through stages of collection, presentation, reduction, and conclusion. The results show that customer satisfaction and loyalty to Lion Air flight services are influenced by several factors, including product quality, price, and service quality. Among these factors, affordable ticket prices are the main factors that encourage customers to make repeat purchases, stay loyal customers, and provide positive recommendations to others. The findings of this study can guide Lion Air's management in formulating effective strategies to improve service quality, strengthen customer loyalty, and maintain its position as a leading airline in Indonesia. Furthermore, it is hoped that further research can produce more comprehensive and useful findings for Lion Air management in improving performance and competitiveness in the aviation industry.